Dampak Penghapusan Subsidi Pupuk terhadap Permintaan Pupuk dan Produksi Padi Nasional - I Wayan Rusastra; Reni Kustiari; Effendi Pasandaran (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1997)
Maintaining rice selfsufficiency in the condition of fiscal austerity can be conducted through technological generation, efficiency improvement, or input subsidy reduction. The objectives of this study is to asses the impact of price liberalization of Urea, TSP, and other chemical fertilizer (KCI and ZA) to the application of those fertilizer and national rice production. The study used the combination of cross-section (five regions) and time series data of 15 years (1979-1993). There are four empirical models under considerations in this study, i.e: rice production function, and demand function of Urea, TSP, and other chemical fertilizers. The system equations of rice production and fertilizer demand functions are estimated simultaneously in order to have an efficient parameter estimates. The research findings indicated that fertilizer price liberalization had positive impact on the structural application of those fertilizers, in which the use of Urea and TSP decline and the use of other chemical fertilizer increases. The structural change of those fertilizer application have positive impact on yield and national rice production, at the magnitude of 5,1 percent. In order to maintain rice productivity (selfsufficiency) and efficient use of national resources, the reduction of Urea and TSP subsidy can be conducted in a faster rate than those ZA's and KCI's For larger rice production improvement, technological breakthrough is really needed in conjunction with managerial skill improvement of the farmers.